Bactericidal efficiency of UVA-active titanium dioxide thin layers on bacteria from food industry environments. (10th November 2017) - Barthomeuf, Marion; Raymond, Perrine; Policarpo, Nyedna; Castel, Xavier; Le Gendre, Laurent; Denis, Martine; Pissavin, Christine
Abstract: Titanium dioxide (TiO2 ) thin layers have been deposited on glass substrates using radio frequency magnetron sputtering technique. The photocatalytic activity of the TiO2 thin layers has been investigated by a methylene blue discolouration test and reveals that films with an anatase structure present the highest performance. Bactericidal activity of the anatase-phase TiO2 layer against food-borne bacteria has then been tested by enumeration of the adherent cells, after adhesion and a subsequent UVA illumination. A decrease of the adherent bacteria number equal to −1.2, −2.6 and −2.3 log is reached for Y. enterocolitica, L. monocytogenes and P. fragi, respectively. SEM observations exhibit bacterial cells with damaged walls for all bacteria. Applied on materials present in the food plants, these TiO2 thin layers may be an effective way for the hygienic conception of the equipment to reduce the biofilm formation and thus, to ensure food safety.